Factors Who Affect Bank Dividend Payout Ratio in Indonesia - Riska Anjari Suherman (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
This study aims to determine the effect of insider ownership, profitability, liquidity, and asset growth partially and simultaneously on bank dividend policy in Indonesia. Factors that tested in this research as the independent variable are Insider ownership, return on asset as a proxy of profitability, loan to deposit ratio as a proxy of liquidity, and asset growth. While the dividend payout ratio is the dependent variable. This research using the descriptive method and the population is the Banks who is listed in Indonesia Capital Market for the period 2013 - 2017 which amounted to 43 companies then become 7 companies after deducting by purposive sampling method. The data analysis that is used in this study is multiple linear regression analysis at the significance level of 5%. The results showed that partially and simultaneously insider ownership, profitability, liquidity, and asset growth effect to dividend payout ratio.